Hexadecyltrimethylammonium-modified fly-ash zeolite for sulfate removal in treated coal-fired power plant effluent - Budput, Anyamanee; Yan, Dickson Y.S.; Htikea, May Thu Than; Khamdahsag, Pummarin; Tanboonchuy, Visanu (Engineering and Applied Science Research, 2023)
This research was conducted primarily to examine sulfate ion (SO42-) removal from aqueous solutions using zeolite NaP1 surface modified with hexadecyltrimethylammonium (HDTMA), or so-called MZ-HDTMA. To be suitable for SO42- removal conditions, the synthetic conditions of MZ-HDTMA were optimized utilizing a Box-Behnken design approach. Experiments were conducted considering three factors that influence synthesis, including the amount of HDTMA cationic surfactant (3.33-6.67 wt%), mixing time (0.5-2 h), and drying temperature (50-80°C). The zeolite NaP1 synthesized from fly ash and MZ-HDTMA were characterized to compare their characteristics using techniques including point of zero charge (pHpzc), scanning electron microscopy (SEM), and x-ray diffraction (XRD). The results from SO42- removal showed that the most significant effect was the weight percentage of HDTMA. Adsorption kinetic studies revealed that modified zeolite had a SO42- removal amount of 8.913 mg/g at equilibrium time and better fitted the pseudo-second-order model (R2 = 0.99). This study established that more than 80% of the SO42- in the aqueous solution was removed.